Utilization of the Indonesia Smart College Card (KIP-K) Scholarship Funds in Supporting the Academic Achievement of Civil Engineering Students at Gunung Leuser University - Pitri, Sari; Yusriman, Yusriman; Harmaini, Harmaini (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
This study aims to analyze the utilization of Indonesia Smart College Card (KIP-K) scholarship funds in supporting the academic achievement of students in the Civil Engineering Study Program at Gunung Leuser University. A descriptive qualitative approach was employed, involving six KIP-K scholarship recipients selected through purposive sampling. Data were collected through semi-structured interviews, observations, and document analysis and were subsequently analyzed using thematic analysis. Data trustworthiness was ensured through source triangulation and methodological triangulation. The findings reveal that KIP-K scholarship funds were primarily utilized to meet academic needs, including the purchase of laptops, books, stationery, internet packages, and other learning-support materials. In addition, the funds were allocated to non-academic needs, such as transportation expenses and daily living costs that contributed to students’ educational continuity. The study also found that some students lacked systematic financial planning, resulting in difficulties managing scholarship funds throughout an academic semester. Nevertheless, KIP-K recipients were able to maintain satisfactory academic performance, as reflected in their cumulative grade point averages, which ranged from good to highly satisfactory categories. These findings suggest that strengthening financial literacy programs among KIP-K recipients is essential to maximize the educational impact of scholarship assistance and sustain academic achievement.